Gains in Life Expectancy by Elimination of Specified Causes of Death in Pakistan (The Pakistan Development Review, 1988)
Death is inevitable. However, efforts have always been made to delay it. Due to the advancement in medical science, the developed countries have succeeded in achieving a considerable increase in the life expectancy of the people. On the other hand, the developing countries are striving hard to follow the same trend. but with lesser success. Constrained by limited resources, health planners have been compelled to set priorities towards the elimination of widespread fatal diseases. The cause specific death rates can provide a measure of the most widely prevalent diseases in the region. An age and cause specific death rate, would give a more refined measure of the same. However, in order to measure the gain in life expectancy by elimination of specific causes of death, the use of the life table technique would be an appropriate one. For example, if 'Malaria' is the largest killer in a region. the application of this technique could provide us with added years of life resulting from the elimination of Malaria. The present study is an attempt to examine the gains in life expectancy at birth as well as for other broad age groups by eliminating specified causes of death.